2019
DOI: 10.13052/jiems2446-1822.2018.005
|View full text |Cite
|
Sign up to set email alerts
|

ISO 55001 – A Strategic Toolfor the Circular Economy – Diagnosisof the Organization’s State

Abstract: Circular economy arises at a time when the needs for the reduction, reuse, recovery and recycling of materials and energy need to consolidate. Today's economy is unsustainable in the short run. The standard ISO 55001 defines a set of requirements that, when implemented and maintained, guarantee the good performance of an organization's asset management, responding to stakeholder needs and expectations and ensuring the value creation and maintenance as well as a global vision of assets in a circular economy.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…To help on the implementation of ISO 55001, Pais et al [27] present a method of diagnosing the state of the organization, that corresponds to a set of surveys in which the evaluation of the responses indicates the position of the company in relation to the application of the standard, the result is a radar map ( Figure 12) where can be seen the position of the organization regarding ISO 55001 implementation. Each question is related with the points presented on the radar chart as follows: A.…”
Section: Asset Management Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…To help on the implementation of ISO 55001, Pais et al [27] present a method of diagnosing the state of the organization, that corresponds to a set of surveys in which the evaluation of the responses indicates the position of the company in relation to the application of the standard, the result is a radar map ( Figure 12) where can be seen the position of the organization regarding ISO 55001 implementation. Each question is related with the points presented on the radar chart as follows: A.…”
Section: Asset Management Diagnosismentioning
confidence: 99%
“…Fig. 12: Radar Map [27] There are several non-exclusive causes that make replacement equipment economical, being deterioration one of them that is manifested by excessive operating and rising maintenance costs. This subject has been researched by several authors, with interesting results, as is shown, in the field of urban passenger transport, by the references [28], [29] and [30].…”
mentioning
confidence: 99%
“…LCC is a commonly used concept mentioned in several standards, like the ISO 15663-1, Petroleum and natural gas industries -Life cycle costing -Part 1: Methodology. The work of Pais et al [19] is in line with [9], as they include a diagnostic model on the state of organizations to help the implementation of ISO 55001.…”
Section: State Of the Art On Asset's Life Cycle And Maintenance Policiesmentioning
confidence: 99%
“…The work of Pais et al [19] is in line with [9], including a diagnostic model on the state of organizations to help the implementation of ISO 55001. Farinha [20] presents some econometric models to evaluate the LCC, including the withdrawal time for medical equipment.…”
mentioning
confidence: 97%